“Pendidikan Profetik pada Masa Nabi Muhammad SAW: Telaah Historis Transformasi Sosial melalui Nilai Tauhid, Humanisasi, dan Liberasi” - Laely Nurhayati (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Prophetic education is an educational approach based on prophetic values ​​that aims to form a person who is faithful, rational, and just. This article aims to historically examine the implementation of prophetic values—tawhid, humanization, and liberation—in education during the time of the Prophet Muhammad SAW and their impact on the social transformation of Arab society. This study uses a qualitative approach with a historical study method through analysis of primary sources (sirah, hadith) and secondary sources (academic literature). The results of the study show that the Prophet's education not only instilled the teachings of tawhid spiritually, but also built awareness of humanity and social justice. This transformation succeeded in changing the structure of jahiliyah society into a civil community based on ethical and transcendental values. This study emphasizes the importance of revitalizing prophetic education in the current Islamic education system to answer modern social and moral challenges.